Contemporaneous interaction between energy consumption, economic growth and environmental sustainability in South Africa: What drives what? - Saint Akadiri, Seyi; Bekun, Festus Victor; Sarkodie, Samuel Asumadu (Elsevier, 2019)
Achieving environmental sustainability while mitigating climate change and its impact has become a global effort This paper offers a new perspective on the kg oil equivalent per capita energy consumed and real income per capita level nexus for South Africa while controlling for the effect of ecological footprint. Using a time series data from 1973 to 2014, the study employed the Autoregressive Distributive Lag model and Toda-Yamamoto procedure for testing Granger causality. Empirical results revealed the significant role of kg oil equivalent per capita energy usage and real output per capita level towards environmental quality or degradation in South Africa. A 1% increase in kg of oil equivalent per capita energy consumed and real income per capita led to 0.167% decrease and 0.172% increase in environmental quality in the short-run. A 1% increase in kg of oil equivalent per capita energy consumed and real income per capita led to 0.542% decrease and 0.558% increase in environmental quality in the long-run. On the direction of predictive relationship, empirical results showed unidirectional causality running from environmental quality to real income per capita, from kg oil equivalent per capita of energy consumed to environmental quality and from kg oil equivalent per capita of energy consumed to real income per capita. Results indicated that environmental pollution in South Africa is not output driven but depends on the unit of kg oil equivalent per capita energy produced and consumed. Depending on the direction of causality between the variables, the policy implication can be examined from the perspective of economic performance, energy saving, and environmental sustainability in the long-run. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: Environmental quality; Energy usage; Ecological footprint; Economic growth; Dynamic causality